Engaging Community Stakeholders for School-Based Physical Activity Intervention (Implicando a actores de la comunidad para la intervención en materia de actividad física desde la escuela) - Jon Salsberg; Soultana Macridis; Enrique Garcia Bengoechea; Ann C Macaulay; Spencer Moore (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Sustainable school-based physical activity intervention is founded on the engaged participation of community individuals and organisational stakeholders who may facilitate or benefit from the intervention actions undertaken. Often in community-based research, intervention ideas are initiated by outside actors. Yet in order to develop and sustain programs successfully, community stakeholders must meaningfully be engaged, take ownership and assume leadership roles. To foster stakeholder engagement, health promotion specialists utilise strategies intended to create a sense of ownership among community stakeholders over the process. In practical terms this means that control over decision-making is actively placed into the hands of the end-users of the action. However, little is understood about how communities take control of the intervention process. Using social network analysis, we focus on a school travel planning project that was initiated from outside the community, and examine the co-evolution of community ownership, influence and decision-making within a multi-stakeholder network over the course of the project. Results show that despite the project’s extra-community origins and its strong initial leadership by a non-community member, new community opinion-leaders emerged as central actors and knowledge leaders within the network over the course of the project’s development. These interim results have implications for how community-academic research and programming partnerships are planned to develop and evaluate health promotion interventions.